AUSÊNCIA DO ACOMPANHANTE EM TEMPO INTEGRAL E SEU EFEITO NA OCORRÊNCIA DE INTERVENÇÕES DESNECESSÁRIAS NO PRÉ-PARTO E PARTO EM MATERNIDADES BRASILEIRAS VINCULADAS À REDE CEGONHA. - GOIABEIRA, Yara Nayá Lopes de Andrade (2021)
Introduction: The presence of a full-time companion is a right guaranteed by law, capable of optimizing the physiology of childbirth, reducing the hospital stay, providing psychological and emotional support to the woman, among other benefits. However, this right has not been fulfilled in its entirety in maternity hospitals linked to Rede Cegonha. Objective: To analyze the absence of a full time companion and its effect on the occurrence of unnecessary interventions in pre-partum and childbirth in Brazilian maternity hospitals linked to Rede Cegonha. Method: A national, cross-sectional study carried out in all Brazilian maternity hospitals linked to the RC of the Unified Health System (SUS – Sistema Único de Saúde), from December/2016 to October/2017. The participants of the study were 5,113 mothers from all regions of the country who had a vaginal birth in one of the 606 maternity hospitals with a regional action plan approved by Rede Cegonha. In the first article, proportions and respective 95% confidence intervals (CI) were estimated, adjusted for the cluster effect, comparing macro-regions by Wald's Chi-square test, and in the second article, a theoretical model was developed using Directed Acyclic Graph, testing the hypotheses by causal inference. The absence of a companion during hospitalization was considered as exposure and the occurrence of unnecessary interventions in pre-partum and delivery as an outcome. Pairing by propensity score and weighting by the inverse probability of exposure were used to balance the groups and estimate the causal effect, through adjusted regression coefficients (RC) and respective 95% CI and (alpha=5%). Results: The presence of a full-time companion occurred in 71.2% of deliveries, being higher among mothers aged 20-35 years, brown, with higher education, married and who gave birth vaginally. Almost 30% of postpartum women did not have a full time companion. Self-declared black women, with less education, single and who were assisted by a medical professional during childbirth had fewer companions. The time of delivery had a greater absence of a companion (70.8%). It was found that 92.1% of women who gave birth vaginally suffered some type of unnecessary interventions in pre-partum and/or delivery. The North, Northeast, and Southeast regions had a higher occurrence of interventions in unaccompanied women. The absence of a companion had an effect on the occurrence of venoclysis (Coef = 0.083; 95% CI 0.037 - 0.129), lithotomy (Coef = 0.144; 95% CI 0.103 - 0.185) and episiotomy (Coef = 0.064; CI 95% 0.022 – 0.105). Conclusion: The presence of a full-time companion in the maternity hospital works as a quality control of professional care, contributing to the reduction of professional behaviors in childbirth care considered harmful and/or ineffective, making them less technical and medicalizing.